Evaluation of Atherogenic Index of Plasma and Lipid Ratios in Patients with Head and Neck Squamous Cell Carcinoma in North Indian Study Group - Dr. Rajesh Kumar, Dr. Deepika Dalal, Dr. Saurabh Kumar Deo, Dr. Neeru Bhaskar, Dr. Kiran Dahiya, Dr. Sukhpal Singh, Vanshika Bhardwaj, Dr. Sanika Baweja (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Cancers have become a leading cause of morbidity and mortality in today’s world.With time the incidence of cancers is rapidly rising. Head and neck carcinomas pose real threatbeing very aggressive in their course and also poor prognosis adds on to their occurrence. India